2006
DOI: 10.3171/spi.2006.4.3.198
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral transforaminal lumbar interbody fusion and bilateral anterior-column fixation with two Brantigan I/F cages per level: clinical outcomes during a minimum 2-year follow-up period

Abstract: Object There are no published reports of unilateral transforaminal lumbar interbody fusion (TLIF) in which two Brantigan I/F cages were placed per level through a single portal to achieve bilateral anterior-column support. The authors describe such a surgical technique and evaluate the clinical outcomes of this procedure. Methods Data obtained in 86 (93.5%) of the first 92 consecutive patients who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 21 publications
0
40
0
1
Order By: Relevance
“…7 Recently, this unilateral PS system has been more frequently employed in combination with transforaminal lumbar interbody fusion (TLIF) rather than in posterolateral fusion and posterior lumbar interbody fusion (PLIF). 8,9 As described above, favorable results have been reported for lumbar fusion in combination with a unilateral PS system. However, little data are available on the biomechanical properties of the system.…”
Section: Introductionmentioning
confidence: 68%
“…7 Recently, this unilateral PS system has been more frequently employed in combination with transforaminal lumbar interbody fusion (TLIF) rather than in posterolateral fusion and posterior lumbar interbody fusion (PLIF). 8,9 As described above, favorable results have been reported for lumbar fusion in combination with a unilateral PS system. However, little data are available on the biomechanical properties of the system.…”
Section: Introductionmentioning
confidence: 68%
“…In spite of this claim, some reports indicate that in actual practice, only 80-90% of the posterior disk space is removed during total diskectomy 11) . Conventional TLIF has been shown to reduce complications; clinical studies with follow-ups between 12 and 64 months have found that fusion rates for TLIF are similar to those expected for other interbody fusion techniques-that is, more than 90% 5,8,12,14,20) . However, the major criticism of unilateral TLIF procedures is that unilateral diskectomy reduces the probability of fusion because of the limitations imposed by using conventional tools and because it is more difficult to remove sufficient disk material during diskectomy and endplate preparation than during PLIF, especially from the contralateral posterior side using a unilateral approach.…”
Section: Discussionmentioning
confidence: 86%
“…All the details are illustrated in Table 2. Discussion TLIF, first described by Harms and Rolinger [16], is currently used increasingly as an alternative procedure for lumbar posterolateral fusion or posterior lumbar interbody fusion (PLIF) [14,[17][18][19]. As with the PLIF procedure, TLIF offers a number of potential benefits, including increased fusion surface area, complete access for medial and lateral decompression and restoration of intervertebral body height [20].…”
Section: Resultsmentioning
confidence: 99%